Silent agency and symbolic authority: negotiating piety and representation among urban Salafi women in Indonesia’s digital sphere - Rofhani, Rofhani; Biyanto, Biyanto (Indonesian Journal of Islam and Muslim Societies, 2026)
This article proposes silent agency as a framework for understanding how urban Salafi women in Indonesia negotiate piety and religious authority within the visibility-driven landscape of social media. Drawing on reflective digital ethnography and narrative– visual analysis of forty-five Instagram posts from three Salafi-oriented accounts, the study demonstrates how these women cultivate a religious presence through anonymity, textual discipline, and non-figurative aesthetics. They do not rely on personal visibility or affective expression. Authority is articulated through scriptural citations, standardized templates, and restrained visual fields grounded in collective norms and standards. These practices reveal a representational logic in which concealment becomes a deliberate epistemic stance, reconfiguring agency beyond the liberal assumptions that link to visibility. By identifying the intertwined operations of visual modesty, symbolic authority, and digital piety, the article demonstrates how Salafi women construct a coherent mode of online participation that aligns with shar‘i commitments while resisting self-exposure. The findings contribute to debates on Muslim women’s digital subjectivities, the aesthetics of Islamic authority, and the politics of non-visibility in the contemporary Islamic public sphere. Artikel ini mengembangkan konsep silent agency untuk menjelaskan bagaimana perempuan Salafi perkotaan di Indonesia menegosiasikan kesalehan dan representasi dalam ruang digital. Dengan menggunakan etnografi digital dan analisis visual naratif dari empat puluh lima postingan Instagram dari tiga akun bertema Salafi, studi ini menunjukkan bahwa bagaimana perempuan Salafi ini menumbuhkan kehadiran agama melalui anonimitas, disiplin tekstual dan estetika non-figuratif. Mereka tidak mengandalkan visibilitas pribadi atau ekspresi afektif. Otoritas diartikulasi melalui kutipan teks-teks suci, standarisasi template, dan visual yang selalu terkendali dan berdasar pada norma-norma kolektif. Praktik ini mengungkakan logika representasional, di mana penyembunyian menjadi sikap epistemik yang disengaja, mengkonfigurasi ulang agency di luar asumsi liberal yang menghubungan visibilitas. Dengan mengidentifikasi ada saling keterkaitan antara visual modesty, symbolic authority, and digital piety, artikel ini menunjukkan bahwa perempuan Salafi membangun partisipasi online yang koheren dengan komitmen shar’i, sambil menolak eksposur diri. Temuan ini berkontribusi pada perdebatan tentang subjektivitas digital perempuan Muslim, estetika otoritas Islam, dan politik non-visibilitas dalam ruang publik Islam kontemporer.